A clinical trial of neuromuscular electrical stimulation in improving quadriceps muscle strength and activation among women with mild and moderate osteoarthritis. - Palmieri-Smith RM; Thomas AC; Karvonen-Gutierrez C; Sowers M (Physical Therapy, 2010)
Background. Neuromuscular electrical stimulation (NMES) has demonstrated efficacy in improving quadriceps muscle strength (force-generating capacity) and activation following knee replacement and ligamentous reconstruction. Yet, data are lacking to establish the efficacy of NMES in people with evidence of early radiographic osteoarthritis. Objective. The purpose of this study was to determine whether NMES is capable of improving quadriceps muscle strength and activation in women with mild and moderate knee osteoarthritis. Design. This study was a randomized controlled trial. Methods. Thirty women with radiographic evidence of mild or moderate knee osteoarthritis were randomly assigned to receive either no treatment (standard of care) or NMES treatments 3 times per week for 4 weeks. The effects of NMES on quadriceps muscle strength and activation were evaluated upon study enrollment, as well as at 5 and 16 weeks after study enrollment, which represent 1 and 12 weeks after cessation of NMES among the treated participants. The Western Ontario and McMaster Universities Osteoarthritis Index and a 40-foot (12.19-m) walk test were used at each testing session. Results. Improvements in quadriceps muscle strength or activation were not realized for the women in the intervention group. Quadriceps muscle strength and activation were similar across testing sessions for both groups. Limitations. Women were enrolled based on radiographic evidence of osteoarthritis, not symptomatic osteoarthritis, which could have contributed to our null finding. A type II statistical error may have been committed despite an a priori power calculation. The assessor and the patients were not blinded to group assignment, which may have introduced bias into the study. Conclusions. Four weeks of NMES delivered to women with mild and moderate osteoarthritis and mild strength deficits was insufficient to induce gains in quadriceps muscle strength or activation. Future research is needed to examine the dose- response relationship for NMES in people with early radiographic evidence of osteoarthritis.